Teaching Music Performance in Higher Education: Exploring the Potential of Artistic Research - Minors, Helen Julia; Östersjö, Stefan; Dalagna, Gilvano; Correia, Jorge Salgado (Cambridge, UK Open Book Publishers, 2024)
Higher Music Performance Education, as taught and learned in universities and conservatoires in Europe, is undergoing transformation. Since the nineteenth century, the master-apprentice pedagogical model has dominated, creating a learning environment that emphasises the development of technical skills rather than critical and creative faculties. This book contributes to the renewal of this field by being the first to address the potential of artistic research in developing student-centred approaches and greater student autonomy. This potential is demonstrated in chapters illustrating artistic research projects that are embedded within higher music education courses across Europe, with examples ranging from instrumental tuition and ensemble work to the development of professional employability skills and inclusive practices.Bringing together diverse and experienced voices working within Higher Music Education but often also as professional performers, this edited collection pairs critical reflection with artistic insight to present new approaches to curricula for teaching interpretation and performance. It calls for greater collaboration between Higher Education and professional music institutions to create closer bonds with music industries and, thereby, improve students’ career opportunities. Teaching Music Performance in Higher Education will appeal to scholars, performers, teachers, but also students whose interests centre on innovative practices in conservatoires and music departments.
Includes bibliographical references and index.
Keywords: Performance; Artistic research; Music education